Cinta Damai Upaya Meminimalisir Konflik dalam Masyarakat - Syamsudhuha Saleh (Fakultas Ushuluddin dan Filsafat Universitas Islam Negeri Alauddin Makassar, 2010)
This paper discusses the concept of peace in the sosiologi of religion it is an attempt to understand the source of based on religion conflict in society. Indonesia is a plural country that has many cultures, ethnics, and religions. This diversity can cause conflict in society on behalf of those issues. Other issues that caused conflict are economic, political, and injustice reasons. Conflict that cause in security in society is contradicted with Islam and other religious. Doctrines Islam is a religion, that does not only promote love in peace, but it also appreciates diversity. One of the most important ways to overcome the problem is education, because it offers value and knowledge transformation to students. The second important ways to overcome the problem is the involvement of religious elites at social, economical, and political aspect. Another important way is the government of Indonesia have to support the implementation of curriculum concerning multicultural education.